(untitled) (Journal of Advanced Research in Social Sciences, 2025)
Research problem: This article examines the role of ethnic leaders in Afghanistan’s political developments during the Republic period (2001-2021) and highlights their influence in various areas. Ethnic leaders, representing diverse ethnic groups in Afghanistan, played a crucial role in shaping the political landscape and balancing traditional power structures with modern state institutions. Methodology: Based on data collected through semi-structured interviews, this research was coded, categorized, and analyzed using grounded theory. Key findings: Ethnic leaders’ footprints can be observed in most of the country’s political, economic, and social transformations and challenges in recent decades. Corruption, factionalism, ongoing insurgencies, financial dependency on foreign aid, and the illegal drug trade were among the major issues that weakened the Afghan government, problems directly linked to ethnic leaders’ actions. Implications: This study concludes that sustainable economic development, good governance, democracy, and genuine political reforms are essential for political stability in Afghanistan. Its findings contribute to a deeper understanding of Afghanistan’s political complexities and offer insights into nation-building and resolving both national and international conflicts.